Binary opposition, chronology of time and female identity in William Faulkners A Rose for Emily - Barani, Forough; Wan Yahya, Wan Roselezam (Australian International Academic Centre, 2014)
In any work of imaginative literature, binary oppositions, the specifics of time and the characterization of the protagonist play some role, no matter how small and insignificant. Reading Faulkner’s short story “A Rose for Emily” in light of the conflicts of the old and the new, the tradition and the traditionless, the chronology of time and its effect on the reader, and the characterization of the female protagonist was indicative of the influence of cultural elements in analyzing the story. While Faulkner was doubtless a major artist in terms of depicting the life of Southerners of the time and changes in the norms and codes of their lifestyle, the reader and the cautious critic also will have a distinct, and often contradictory, interpretation of a given text from the point of view and theoretical perspective that he/she adopts.